Association of short-term exposure to ambient PM1 with total and cause-specific cardiovascular disease mortality. (November 2022) - Xu, Ruijun; Wei, Jing; Liu, Tingting; Li, Yingxin; Yang, Chunyu; Shi, Chunxiang; Chen, Gongbo; Zhou, Yun; Sun, Hong; Liu, Yuewei
Graphical abstract: Highlights: PM1 exposure was associated with an increased odds of cause-specific CVD mortality. The excess CVD deaths attributable to ambient PM1 exposure was considerable. Older adults may be more susceptible to ambient PM1 exposures. This study provides quantitative data for formulating air quality standards for PM1 . Abstract: Background: The acute effects of exposure to ambient particulate matter with an aerodynamic diameter ≤1 μm (PM1 ) on cardiovascular disease (CVD) mortality remain unclear. Objectives: To investigate whether short-term exposure to ambient PM1 was associated with mortality from total and/or cause-specific CVDs, and estimate the excess mortality. Methods: A time-stratified case-crossover study was conducted among 1, 081, 507 CVD deaths in Jiangsu province, China from 2015 to 2020. We assessed daily residential ambient PM1 exposures using a validated grid dataset for each subject. Conditional logistic regression models and distributed lag linear or nonlinear models were employed to quantify the association of PM1 exposure with mortality during the same day of CVD death and 1 day prior. Results: Each 10 μg/m 3 increase of PM1 exposure was significantly associated with a 1.46 % (95 % confidence interval: 1.28 %, 1.65 %), 1.95 % (1.28 %, 2.63 %), 1.16 % (0.86 %, 1.47 %), 1.41 % (1.13 %, 1.69 %), and 1.83 % (1.37 %, 2.30 %) increased odds of mortality from total CVDs, hypertensive diseases (HDs), ischemic heart diseases (IHDs), stroke, and sequelae of stroke, respectively (all p <0.05). No significant association was identified with mortality from pulmonary heart disease or chronic rheumatic heart diseases. The excess fraction of total CVD mortality attributable to PM1 exposure was 5.71 %, while the cause-specific excess fractions ranged from 4.98 % for IHDs to 7.46 % for HDs. Significantly higher excess fractions were observed for total and certain cause-specific CVD mortality in adults 80 years or older. Conclusions: We found that short-term exposure to ambient PM1 was significantly associated with an increased odds of mortality from total and specific CVDs and may lead to considerable excess mortality especially among older adults. Our findings highlight a potential approach to prevent premature CVD deaths by reducing PM1 exposures and provide essential quantitative data for the development of future air quality standards for ambient PM1 .